Insights into the molecular mechanisms of ABC transporters and membrane insertases - Fiorentino, F (2020)
Membrane proteins have a pivotal role in cellular homeostasis given their strategic position and involvement in pathways such as small molecules transport and interaction with ligands leading to downstream responses. In this thesis, I describe the application of mass spectrometry approaches to elucidate the structure, dynamics and regulation of membrane protein complexes, including ABC transporters and membrane insertases. The employment of native mass spectrometry (nMS) to membrane proteins has allowed the examination of non-covalent interactions, as described in Chapter 2 where the interaction between ABC importers and their cognate substrate binding proteins (SBPs) was analysed and the mechanism of transport of these complexes was clarified. This analysis indicated that substrate and nucleotide binding destabilise the interaction between the type II importer BtuCD and the SBP BtuF, while has no effect on the interaction between type I importer ModBC and the SBP ModA. Similarly, nMS allowed the elucidation of protein-lipid and protein-substrate interactions of the LPS transporter LptB2FG, suggesting that cardiolipin competes for LPS binding and nucleotide binding increases affinity for the substrate. The combination of nMS and cryo-electron microscopy (cryo-EM) allowed further elucidation on the structure of this protein complex and its interactions with LptC and LptA. The combination of nMS with hydrogen-deuterium exchange mass spectrometry (HDX- MS) and molecular dynamics (MD) simulations yielded information on the conformational dynamics of the outer membrane LPS translocon LptDE, showing opposite effects of substrate and antimicrobial peptide thanatin. Indeed, while LPS induces opening of the periplasmic domain of LptD, thanatin stabilises this region, acting as a non-competitive inhibitor of LPS transport. In Chapter 5, nMS is again combined to cryo-EM, as well as lipidomics and in vivo studies to define the structure and subunit stoichiometry of the eukaryotic tail-anchored protein insertase complex, revealing the contribution of phosphatidylinositol binding on the stabilisation of the complex.